2000
DOI: 10.1345/aph.19144
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition Support in Acute Pancreatitis

Abstract: Current evidence suggests that the enteral rather than parenteral route should be used to provide nutrition to patients with acute pancreatitis. Parenteral nutrition should be reserved for patients in whom nasojejunal feeding is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…5,6 Enteral feeding seems more effective than parenteral nutrition, especially with respect to maintaining the structural and functional integrity of the gut. 12,13 However, (additional) parenteral nutrition seems indispensable in most patients with severe AP, when increased demand for calories and substrates cannot be met by enteral feeding, eg, in the presence of ileus. Thus, optimization of parenteral nutrition and immunonutrition remain an issue.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Enteral feeding seems more effective than parenteral nutrition, especially with respect to maintaining the structural and functional integrity of the gut. 12,13 However, (additional) parenteral nutrition seems indispensable in most patients with severe AP, when increased demand for calories and substrates cannot be met by enteral feeding, eg, in the presence of ileus. Thus, optimization of parenteral nutrition and immunonutrition remain an issue.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of food in the stomach and duodenum elicits gastropancreatic and duodenopancreatic reflexes that result in the stimulation of pancreatic exocrine secretion. However, these effects are insignificant when nutrients are delivered directly into the jejunum [16][17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps less clear is the route by which nutrition should be administered. [92][93][94][95] Total parenteral nutrition (TPN) has been the standard of therapy for many years because it accomplished 'pancreatic rest,' a concept eluding to the reduction of pancreatic secretions, and thereby limiting peripancreatic release of digestive enzymes. Some studies also suggested that early oral feeding or nasogastric feeding may increase risk of pancreatic infection and worsening the disease.…”
Section: Nutritional Supportmentioning
confidence: 99%
“…The culmination of these detrimental effects has been associated with a greater risk for septic complications and adds significant expense. [92][93][94][95] With the potential pitfalls of parenteral nutrition (PN), several randomized clinical trials have shown that enteral nutrition (EN) can be safely administered via nasojejunal feeding tubes in patients with AP with no significant detrimental effects. [97][98][99] Jejunal feeding was demonstrated not to increase pancreatic secretions, as nutrient delivery occurs in areas devoid of cholecystokinin (CCK)-releasing cells.…”
Section: Nutritional Supportmentioning
confidence: 99%